Land use/land cover change detection along the coastline of Nigeria and its probable causes - Akinyele Olatunji, Olubusayo (International Journal of Advanced Geosciences, 2020)
The Nigerian coastline has been subjected to studies on land use/land cover changes, using satellite images, for three decades. This paper is borne out of the need to understand the dynamics of coastal management. The study aims at assessing land use-land cover changes along coastline in Nigeria from 1986 to 2016 using multi-day satellite imageries. The satellite data were used to extract land use/cover changes and to map the physical extent of the coastal areas of Nigeria for the three-time series during the same season. Urban/built up areas, water and vegetation are the three land use/cover classes of interest along the Nigerian coastline. The urban/built up area class increased from 8.9% in 1986 to 13.7% in 2000, and then 23% in 2016. On the other hand, vegetation decreased from 55% in 1986 to 49% in 2000 and then 43% in 2016. In contrast, water class increased from 36% in 1986 to 37% in 2000, and then decreased to 32.7% in 2016. Considering observations made from this study, it is therefore recommended that the appropriate government agencies, coastal managers and urban planners should promote afforestation along with other mitigation measures, to reduce the adverse effects of human develop-ment on the ecosystem.